Performance in beam tests of irradiated Low Gain Avalanche Detectors for the ATLAS High Granularity Timing Detector. (1st September 2022) - Agapopoulou, C.; Alderweireldt, S.; Ali, S.; Ayoub, M.K.; Benchekroun, D.; Castillo García, L.; Chan, Y.H.; El Jarrari, H.; Falou, A.; Ferreira, A.; Gkougkousis, E.L.; Grieco, C.; et al.
Abstract: The High Granularity Timing Detector (HGTD) will be installed in the ATLAS detector to mitigate pile-up effects during the High Luminosity (HL) upgrade of the Large Hadron Collider (LHC) at CERN. The design of the HGTD is based on the use of Low Gain Avalanche Detectors (LGADs), with an active thickness of 50 μm, that allow to measure with high-precision the time of arrival of particles. The HGTD will improve the particle-vertex assignment by measuring the track time with a resolution ranging from approximately 30 ps at the beginning of the HL-LHC operations to 50 ps at the end. Performances of several unirradiated, as well as neutron- and proton-irradiated, LGAD sensors from different vendors have been measured in beam test campaigns during the years 2018 and 2019 at CERN SPS and DESY. This paper presents the results obtained with data recorded by an oscilloscope synchronized with a beam telescope which provides particle position information within a resolution of a few μm. Collected charge, time resolution and hit efficiency are presented. In addition to these properties, the charge uniformity is also studied as a function of the position of the incident particle inside the sensor pad.